Praktik Kekerasan Seksual Di Kampus: Studi Fenomenologi Tentang Dampak Dan Relevansinya Pada Pembelajaran IPS - annisa eka febriyanti (Program Studi S1 Pendidikan IPS, Universitas Negeri Surabaya, 2026)
This study aims to reveal the practice of symbolic sexual violence on campus, including forms such as sextortion, catcalling, and cyber sexual harassment, while analyzing its impact on students and its relevance to Social Studies (IPS) learning. The research employs a qualitative phenomenological approach, with data collected through in-depth interviews, observations, and documentation involving both victims and Social Studies students as informants. The analysis is grounded in Pierre Bourdieu’s theory of symbolic power and Bronfenbrenner’s ecological systems theory to understand the dynamics of power relations, the psychological, social, and academic impacts, as well as the interaction between individuals and their environments. The findings indicate that symbolic sexual violence on campus has significant effects on students, including psychological trauma, decreased self-confidence, academic setbacks, and social marginalization. Sextortion places students in academic and moral dilemmas, catcalling creates a sense of insecurity while reinforcing patriarchal culture, and cyber sexual harassment extends violence into the digital sphere, which is more difficult to regulate. The relevance to Social Studies learning lies in its role in fostering awareness of values, norms, gender equality, and healthy social relations. Therefore, Social Studies can serve as a critical educational tool to prevent, reduce, and address symbolic sexual violence in higher education.